2015
DOI: 10.1111/echo.12912
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Severe Tricuspid Regurgitation on Accuracy of Echocardiographic Pulmonary Artery Systolic Pressure Estimation

Abstract: The results of the study show that in patients with PAH, the presence of severe TR is associated with an overestimated PASP measurement on echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
(56 reference statements)
0
16
1
4
Order By: Relevance
“…However, many studies in humans have reported inaccuracies when pulmonary artery systolic pressure with TRPG is assessed by Doppler echocardiography rather than right heart catheterization, reporting both underestimation and overestimation . In addition, severe TR may affect the estimation of pulmonary artery systolic pressure by Doppler echocardiography …”
Section: Discussionmentioning
confidence: 99%
“…However, many studies in humans have reported inaccuracies when pulmonary artery systolic pressure with TRPG is assessed by Doppler echocardiography rather than right heart catheterization, reporting both underestimation and overestimation . In addition, severe TR may affect the estimation of pulmonary artery systolic pressure by Doppler echocardiography …”
Section: Discussionmentioning
confidence: 99%
“…Possible explanation is that the larger regurgitant volume, the more congestion in inferior vena cava, which leads to an overestimation of RAP. Ozpelit et al . also mentioned that RAP was the main reason for an overestimated sPAP in patients with severe TR, but they thought the maximal velocity of TR jet did not affect sPAP.…”
Section: Discussionmentioning
confidence: 99%
“…As recommended by ESC and ASE guidelines, 16,17 the LAV index, rather than the LA area index, was selected as the measurement of LA size to be included in the multivariate analysis. Because the SPAP is not always available and may be erroneous, 19 The multivariate analysis (Table 2) showed that the presence of larger RA than LA and SmRV were significant predictors of mortality and that the results were affected by SPAP and CVP. Larger RA than LA had a low sensitivity 20%, but high specificity 94%, for mortality with a negative and positive predictive value of 36% and 88%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As recommended by ESC and ASE guidelines, the LAV index, rather than the LA area index, was selected as the measurement of LA size to be included in the multivariate analysis. Because the SPAP is not always available and may be erroneous, a multivariate analysis without SPAP and CVP was also performed. Spearman's rank correlation coefficient ( r ) was used for bivariate correlation.…”
Section: Methodsmentioning
confidence: 99%